1965
DOI: 10.2466/pms.1965.20.2.335
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Perceptual-Motor Dysfunction in Children: A Factor Analytic Study

Abstract: Analysis of test scores made by 100 children with and 50 without suspected perceptual deficits lead to hypothesizing five syndromes characteristic of dysfunction: (a) developmental apraxia, distinguished by deficits in motor planning, tactile perception and finger identification; (b) tactile, kinesthetic and visual perceptual dysfunction in form and position in space; (c) tactile defensiveness, demonstrated by hyperactive-distractible behavior, faulty tactile perception and defensive responses to tactile stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(78 citation statements)
references
References 21 publications
4
70
0
4
Order By: Relevance
“…The following terms used over the years to describe an individual with motor difficulties have been terms such as "minimal cerebral palsy"; "minimal cerebral dysfunction" (Bax & MacKeith ,1963) although this was used to describe children with wider deficits than just motor difficulties ;"perceptual-motor dysfunction" (Ayres, 1965), and then Brenner and colleagues (1967) in the BMJ described" vi suomotor disability in school children" . The descriptors have tried to highlight the potential underlying deficits such as perceptual-motor difficulties (Domrath, 1968), suggesting problems in perceptual-motor integration.…”
Section: (Pages Not Available)mentioning
confidence: 99%
See 1 more Smart Citation
“…The following terms used over the years to describe an individual with motor difficulties have been terms such as "minimal cerebral palsy"; "minimal cerebral dysfunction" (Bax & MacKeith ,1963) although this was used to describe children with wider deficits than just motor difficulties ;"perceptual-motor dysfunction" (Ayres, 1965), and then Brenner and colleagues (1967) in the BMJ described" vi suomotor disability in school children" . The descriptors have tried to highlight the potential underlying deficits such as perceptual-motor difficulties (Domrath, 1968), suggesting problems in perceptual-motor integration.…”
Section: (Pages Not Available)mentioning
confidence: 99%
“…However the more descriptive term "motor impaired" was used by Whiting, Clarke and Morris (1969). Ayres (1965) referred to clumsiness as developmental dyspraxia. Illingworth, (1968), Dare and Gordon (1970) at around the same time was using the term the 'clumsy child'.…”
Section: (Pages Not Available)mentioning
confidence: 99%
“…It does not, however, recognize that movement is organized according to the object used or the environment. The sensorimotor approach, originating from the research of Ayres (1965) and further developed by others [e.g. Case-Smith (2005)] is based on theories of a child's healthy development through a series of motor skill 'milestones'.…”
Section: Task-specifi C Training: How Does It Relate To Current Intermentioning
confidence: 99%
“…Rhesus monkeys were used because of the large amount of available data on their behavior and development in laboratory settings (Harlow & Harlow, 1969;Suomi, 1997) A. Jean Ayres (1964), an occupational therapist and educational psychologist, coined the term "tactile defensiveness" to characterize the behavioral correlates of a pattern described as "feelings of discomfort and a desire to escape the situation when certain types of tactile stimuli are experienced" (1964, p. 8). Ayres showed that tactile defensiveness or overresponsiveness to tactile stimuli was consistently related to hyperactive and distractible behavior in children (Ayres, 1965(Ayres, , 1966(Ayres, , 1969(Ayres, , 1972. Overresponsiveness to tactile stimuli is easily recognized in children (McIntosh, Miller, Shyu, & Dunn, 1999) and there has been some success in treating it with sensory-based interventions (Ayres & Tickle, 1980;Mailloux, 2001;Miller, Wilbarger, Stackhouse, & Trunnell, 2002;.…”
mentioning
confidence: 99%